2017
DOI: 10.7196/samj.2017.v107i2.10849
|View full text |Cite
|
Sign up to set email alerts
|

Burden, genotype and phenotype profiles of adult patients with sickle cell disease in Cape Town, South Africa

Abstract: Background. An exponential increase in the number of sickle cell disease (SCD) patients in paediatric services in Cape Town, South Africa, has been reported. The trend in adult/adolescent services has not been investigated. Objectives. To evaluate epidemiological trends of SCD and the profile of patients affected by SCD attending the Haematology Clinic at Groote Schuur Hospital (GSH), Cape Town. Methods. (i)A retrospective review of the number of SCD patients over the past 20 years; (ii) a cross-sectional anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
(50 reference statements)
0
3
0
2
Order By: Relevance
“…Reasons for partially satisfied N (%) Difficulty understanding the language used in orientation 26 (33,3) Lack of preparation of the physiotherapy team 15 (22) Precarious resources for dental treatment 19 (59,5)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for partially satisfied N (%) Difficulty understanding the language used in orientation 26 (33,3) Lack of preparation of the physiotherapy team 15 (22) Precarious resources for dental treatment 19 (59,5)…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, the access and quality of care provided to people with sickle cell disease by the Primary Health Care network and the Urgency and Emergency Network need to be improved and this improvement is directly related to the training of health teams. problem [1][2][3]. Originally from Africa, it was brought to Brazil by the forced migration of slaves, most often affecting black and brown people.…”
Section: Introductionmentioning
confidence: 99%
“…Three candidate gene studies reported investigations into the genetic associations of SCD-related phenotypes in a cohort from Cameroon. The phenotypes analyzed in these studies included fetal hemoglobin levels (Pule et al, 2015;Pule, Bitoungui et al, 2017;Pule, Mnika et al, 2017), renal dysfunction (Geard et al, 2017), vaso-occlusive crises and the frequency of hospitalization (Wonkam et al, 2018). Genetic investigations into SCD also included a study on the impact of the drug hydroxyurea (HU) on miRNA expression in peripheral blood isolates of SCD patients (Mnika et al, 2019).…”
Section: Genetics and Genomics Studiesmentioning
confidence: 99%
“…• Apenas uma escassa minoria de participantes (3,1%) (18,8) 4 (12,5) 5 (15,6) 11 (34,4) 5 (15,6) 1 (3,1) 2 (33,3) 1 (25, Fonte: A própria autora.…”
Section: Conclusãounclassified
“…Thirty-four people with SCD were recruited using the "snowball samplimg" method and subjected to a semi-structured interview with collection of demographic, clinical, relationship and satisfaction with health care data. About 44.0% were not included in the Primary Health Care network, which did not provide various procedures / Introdução A doença falciforme (DF) é uma das doenças hereditárias monogênicas de maior prevalência no Brasil e no mundo, sendo considerada importante problema de saúde pública[1][2][3] .Originária da África, foi trazida ao Brasil pela migração forçada de escravos, afetando mais frequentemente negros e pardos. De acordo com o Programa Nacional de Triagem Neonatal, estima-se que no Brasil nasçam, por ano, 3.500 crianças com DF e 200 mil com o traço falciforme4-6 .…”
unclassified